Pelanggaran Pemilu Legislatif 2004 - Cahyono, Heru (Jurnal Penelitian Politik, 2004)
In general, the campaign period in the legislative election has passed in a safe and orderly way. But, in the whole process o f general election, we stillfind many basic problem ofviolation. There are many violations consists of administrative violations and criminal violations. The political parties still using public funds and facilities fo r their own interests. People alleged that all big parties have been involved in someform o f vote-buying, known as money politics which included the distribution of free basic needs, free medical Services and transportation fees. Thisfact contrary to the agreement signed by the political party before the 2004 election day o f which agree to avoid any type and motives of violence in order to reach objectives and to settle problems. The Election Supervisory Committees (Panwaslu) -which is established with the main purpose o f supervising elections— failed to carn’ out an effective supervising especially in money politics violation and manipulation o f vote count result.